Poisons : an introduction for forensic investigators - George, David J. (Boca Raton : CRC Press, 2017)
"A unique book on recognition and investigation of criminal poisoning for investigators of all backgrounds and stages of their careers.Poisons: An Introduction for Forensic Investigators is a concise yet comprehensive overview of toxicants and unanticipated circumstances in which poisoning occurs. This book expands awareness of poisoning possibilities, heightens recognition of the toxic potential of many substances, and provides information to aid in focusing investigations. Poisons discusses life-threatening toxic substances and agents that modify behavior to achieve criminal goals. These include drugs that facilitate sexual assaults and robberies, and those found in medical child abuse and drug-product tampering.More than 230 case studies illustrate both unintentional and intentional poisoning and highlight situations where poisoning may not immediately be apparent. Information is included in pertinent criminal poisoning cases to illustrate the temperament of poisoners, their relationship to victims, their basis for poison selection, and their method of administration. Since Poisons is written by a single author, the discussions, format, educational level, and terminology remain consistent to aid crime scene investigators, homicide detectives, forensic scientists, death investigators, toxicologists, medical examiners, attorneys, and students. The book's more than 650 references are an asset to frame knowledge as well as a resource to return to again and again."--Provided by publisher.
part, I Poison / David J. George -- chapter 1 Poison and Poisoning / David J. George -- chapter 2 Poison Exposure / David J. George -- chapter 3 Poison Absorption / David J. George -- chapter 4 Poison Biodisposition / David J. George -- chapter 5 Poison Detection / David J. George -- chapter 6 Poisoning Treatment / David J. George -- part, II Potential Poisons / David J. George -- chapter 7 Arsenic / David J. George -- chapter 8 Carbon Monoxide / David J. George -- chapter 9 Cyanide / David J. George -- chapter 10 Ethylene Glycol / David J. George -- chapter 11 Nicotine / David J. George -- chapter 12 Strychnine / David J. George -- chapter 13 Thallium / David J. George -- chapter 14 Aspirin / David J. George -- chapter 15 Acetaminophen / David J. George -- chapter 16 Alcohol / David J. George -- chapter 17 Opioids / David J. George -- chapter 18 Antidepressants / David J. George -- chapter 19 Benzodiazepines / David J. George -- chapter 20 Stimulants / David J. George -- chapter 21 Emerging Recreational Psychotropics / David J. George -- chapter 22 Food Poisoning / David J. George -- chapter 23 Plants and Mushrooms / David J. George -- chapter 24 Pesticides / David J. George -- part, III Poisoning / David J. George -- chapter 25 Accidental Poisoning / David J. George -- chapter 26 Suicidal Poisoning / David J. George -- chapter 27 Homicidal Poisoning / David J. George -- chapter 28 Poisonous Women / David J. George -- chapter 29 Health Care Serial Poisoners / David J. George -- chapter 30 Hospitalized Patients Poisoned by Visitors / David J. George -- chapter 31 Medical Child Abuse and Homicide / David J. George -- chapter 32 Drug Abuse Fatalities / David J. George -- chapter 33 Celebrity Drug Deaths / David J. George -- chapter 34 Drug-Facilitated Crimes / David J. George -- chapter 35 Drug-Facilitated Sexual Assault / David J. George -- chapter 36 Drug Product Tampering / David J. George -- chapter 37 Assassination / David J. George -- chapter 38 Multiple Victim Poisonings / David J. George.
Keywords: Accidental poisoning; Poisoning; Poisons